Preparation method of double-monatomic and nanoparticle co-modified carbon nitride

By co-modifying carbon nitride by Ru-Pd bimetallic single atoms in combination with Pd nanoparticles, the limitation of the M-N4 configuration is broken, and the asymmetric low-coordination structure is formed, which significantly improves the photocatalytic activity and CO2 reduction performance.

CN119819346APending Publication Date: 2025-04-15JIANGSU TOUTE INTELLIGENT TECH CO LTD +4
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510022419.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The M-N4 configuration of existing carbon nitride-based single-atom catalytic materials has serious limitations on the electronic structure regulation of active metal sites, resulting in limited improvement of catalytic activity and limited improvement of catalytic performance of a single active center.

Method used

The method of co-modifying carbon nitride by Ru-Pd bimetallic single atoms in combination with Pd nanoparticles is used to form a structure in which asymmetric low-coordinated bimetallic single atoms and nanoparticles coexist.

Benefits of technology

It significantly promotes the separation/transfer of photoexcited carriers, enhances the adsorption/activation of CO2, reduces the energy barrier of *COOH, improves photocatalytic activity, and realizes the efficient utilization of metal resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819346A_ABST
    Figure CN119819346A_ABST
Patent Text Reader

Abstract

A preparation method of Ru-Pd bimetal monatomic synergistic Pd nanoparticle co-modified carbon nitride comprises the following steps: 1) preparing a mixed aqueous solution from ruthenium trichloride and urea, transferring the mixed aqueous solution to a centrifuge tube, rapidly freezing with liquid nitrogen, freeze-drying the frozen mixed solution by using a freeze-drying machine, performing one-step pyrolysis to obtain a precursor, and drying the precursor by using a drying machine to obtain the Ru-Pd bimetal monatomic synergistic Pd nanoparticle co-modified carbon nitride; the pyrolysis condition is that the pyrolytic reaction is performed in a muffle furnace at 550 + / -20 DEG C for 3 + / -1 h, and a product is collected after being ground; 2) placing the product in a 0.5 M sulfuric acid solution, carrying out magnetic stirring treatment for about 24 hours, then carrying out centrifugal washing until the product is neutral, and carrying out freeze drying to obtain a semi-finished product; 3) dispersing the semi-finished product in absolute ethyl alcohol, dropwise adding a palladium nitrate dihydrate solution under magnetic stirring, and continuously stirring for 6 + / -1 h; and an excellent effect can be achieved when the photocatalyst is used for photocatalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new materials and relates to a preparation method of carbon nitride co-modified by double single atoms and nanoparticles, in particular, a preparation method of carbon nitride co-modified by Ru-Pd double metal single atoms and Pd nanoparticles. Background Art

[0002] Single-atom materials are a type of single-atom modified materials obtained by anchoring atomically dispersed metal atoms on the corresponding modified support material. In recent years, single-atom materials have benefited from their maximized atomic utilization efficiency, unique geometric coordination structure, adjustable electronic properties and site-specific activity, resulting in their outstanding performance in some reactions. At the same time, single-atom materials are conducive to reducing material costs and efficient resource utilization, which is particularly important for applications involving precious metals. Therefore, single-atom materials have received extensive attention in the fields of photoelectrochemistry, organic synthesis, pollutant degradation, biomedicine, etc. Especially in the field of artificial photosynthesis, isolated metal atoms anchored on traditional semiconductor catalysts can serve as catalytic active sites for reactions, and their unique coordination configuration and electronic structure can improve the inherent activity of each metal reaction site, so that they usually show excellent reactivity and selectivity that cannot be achieved on metal surfaces. Therefore, single-atom modified materials are an emerging type of artificial photosynthesis materials with broad application prospects, and are also a very ideal platform for exploring the relationship between structure-catalytic performance and studying catalytic mechanisms at the atomic level. Among the many single-atom modified photocatalytic materials, graphitized carbon nitride-based single-atom photocatalytic materials are a class of single-atom materials that have been very popular in recent years because of their low cost, simple synthesis, suitable band gap, rich elements, high chemical stability, and rich nitrogen atoms that can effectively capture metal atoms to form metal-nitrogen coordination structures. However, for most of the carbon nitride-based single-atom catalytic materials currently developed, the single-atom site coordination configuration synthesized by conventional methods is basically a planar symmetrical M-N4 (M refers to metal) configuration. Although this M-N4 configuration improves the catalytic performance of carbon nitride to a certain extent, studies have shown that this highly symmetrical M-N4 configuration actually imposes severe restrictions on the electronic structure adjustment of the active metal site, thereby limiting the further improvement of the catalytic activity. Therefore, in order to break this constraint and accurately adjust the electronic structure of the active site, a series of coordination engineering strategies have been developed for the M-N4 configuration, including adjusting the coordination number and coordination atom type of the active site, introducing hetero-coordinated atoms in the axial direction, and doping heteroatoms in the second coordination shell. In addition, the study found that breaking local symmetry can promote the adsorption / activation of CO2 and intermediates, and optimize CO2 reduction towards a highly selective and highly active reaction path. Therefore, in theory, it is feasible to prepare highly active CO2 reduction to CO photocatalysts by pre-constructing a local planar symmetrical M-N4 configuration active center and then using a symmetry breaking strategy. However, regardless of whether the single-atom active site is symmetrical or asymmetrical, a single active center usually has limited improvement on catalytic performance. Constructing multiple active centers at the same time, such as the coexistence of double single atoms and nanoparticles, is an effective strategy to improve catalytic performance by utilizing the synergistic effect between active sites.Therefore, it is very necessary to develop a simple, efficient, energy-saving preparation method for asymmetric low-coordinated bimetallic single atoms and nanoparticles co-modified carbon nitride with high activity and selectivity. Summary of the invention

[0003] The purpose of the present invention is to provide a preparation method of Ru-Pd bimetallic single atoms and Pd nanoparticles co-modified carbon nitride, which prepares Ru and Pd bimetallic single atoms and Pd nanoparticles co-modified carbon nitride nanomaterials under original simple operation steps.

[0004] The technical solution of the present invention is a preparation method of double single atom and nanoparticle co-modified carbon nitride, which uses two precursor materials - ruthenium trichloride and urea, which are prepared into a mixed aqueous solution in a molar ratio of 1:150000-1:28000 and transferred to a centrifuge tube for rapid freezing with liquid nitrogen. Water is used as a solvent, and the ruthenium trichloride aqueous solution is added to the urea aqueous solution to prepare a mixed solution. The frozen mixed solution is then freeze-dried using a freeze dryer, and the obtained powder is ground and transferred to an alumina crucible with a lid or wrapped in tin foil, and then a precursor is obtained through a pyrolysis step. The pyrolysis conditions are pyrolysis reaction in a muffle furnace at 550±20°C for 3±1h. The product is collected after being ground, and then the product is placed in a 0.5M sulfuric acid solution and magnetically stirred for about 24h, followed by centrifugal washing to neutrality and freeze drying to obtain a Ru single atom modified carbon nitride semi-finished product; the sulfuric acid treatment step is to remove unstable metal species such as ruthenium single substance particles, ruthenium oxide, etc. If these species are present, they react with sulfuric acid to form sulfates, and subsequent washing can wash away possible impurities, and the final product does not contain sulfides;

[0005] The palladium nitrate dihydrate with a mass ratio of 1:38-1:12 and the semi-finished product are uniformly dispersed in anhydrous ethanol under continuous stirring for 6±1h under magnetic stirring, and the resulting suspension is placed in a 70±10℃ oven for drying for 12±1h, and the dried product is transferred to a covered quartz ark and placed in a tube furnace in an Ar atmosphere for annealing at 300±20℃ for 1.5±0.5h, and finally, after grinding, centrifugal washing and freeze drying, the Ru-Pd bimetallic single atom and Pd nanoparticle co-modified carbon nitride nanomaterial is obtained. This method only requires simple pyrolysis and impregnation annealing steps to obtain double single atoms and nanoparticles co-modified carbon nitride, and the key is that a structure in which asymmetric low-coordinated bimetallic single atoms and metal nanoparticles coexist can be formed.

[0006] The key to this method is: (1) two precursor materials - an appropriate amount of ruthenium trichloride and an appropriate amount of urea are mixed into a mixed solution and rapidly frozen under liquid nitrogen, then placed in a freeze dryer for freeze drying, and then transferred to a muffle furnace for pyrolysis reaction. The pyrolysis product is treated with sulfuric acid and washed and freeze-dried to obtain a semi-finished product; (2) an appropriate amount of palladium nitrate dihydrate and an appropriate amount of the above semi-finished product are uniformly dispersed in anhydrous ethanol to obtain a suspension, which is then placed in an oven for drying. The dried product is placed in a tubular furnace in an Ar atmosphere for re-annealing. This simple preparation method may be applied to more types of appropriate metal salts and urea precursors, first pyrolyzed and then impregnated and annealed to synthesize asymmetric low-coordinated bimetallic single atoms and nanoparticles co-modified carbon nitride nanomaterials. There are lone pairs of electrons on the nitrogen atoms in the urea molecule, which can interact with the empty orbits of the metal ions to form stable coordination bonds. Therefore, Pd ions can be combined with urea; in the pyrolysis step, the principle of the amount of metal salt used to urea is: the molar ratio of metal salt to urea is 1:150000-1:28000. In the immersion annealing step, the principle of the amount of metal salt used to pyrolyze the semi-finished product of the first metal salt and urea is: the mass ratio of metal salt to the semi-finished product obtained by pyrolysis is 1:38-1:12.

[0007] The present invention provides a use of asymmetric low-coordinated Ru-Pd bimetallic single atoms in cooperation with Pd nanoparticles to co-modify carbon nitride, that is, asymmetric low-coordinated Ru and Pd bimetallic single atoms in cooperation with Pd nanoparticles to co-modify carbon nitride for photocatalytic reduction of carbon dioxide. The results show that the synergistic effect between asymmetric low-coordinated Ru-Pd bimetallic single atoms and Pd nanoparticles significantly promotes the separation / transfer of photoexcited carriers, enhances the adsorption / activation of CO2, and reduces the formation energy barrier of *COOH, thereby leading to excellent photocatalytic activity. Moreover, the presence of adjacent Pd nanoparticles makes electrons more enriched in the asymmetric Ru single atom site, making it a key active site with excellent activity. Therefore, asymmetric low-coordinated Ru-Pd bimetallic single atoms in cooperation with Pd nanoparticles to co-modify carbon nitride nanomaterials is a good photocatalytic material. Using it for photocatalytic reduction of carbon dioxide can achieve good results.

[0008] The asymmetric low-coordinated Ru and Pd bimetallic single atoms prepared in this way and co-modified with Pd nanoparticles can be used in the field of photocatalysis, such as photocatalytic carbon dioxide reduction.

[0009] Beneficial effects: Urea and ruthenium trichloride are mixed into a solution and freeze-dried and placed in an alumina crucible. A Ru single atom-modified carbon nitride semi-finished product is obtained through a one-step pyrolysis step and sulfuric acid treatment. The steps are simple and convenient. The uniform dispersion of metal atoms is fully ensured by solution mixing and rapid freezing. The sulfuric acid treatment effectively eliminates possible particle aggregation and unstable sites. Another raw material, urea, is cheap, stable and non-toxic. At the same time, the Ru single atom-modified carbon nitride semi-finished product and palladium nitrate dihydrate are impregnated and dried, re-annealed, centrifuged and washed, and freeze-dried to obtain asymmetric low-coordinated Ru-Pd bimetallic single atoms and Pd nanoparticles co-modified carbon nitride nanomaterials. This structure is very beneficial for photocatalysis. The activity of photocatalytic carbon dioxide reduction to produce CO and CH4 is improved; in addition, the formation of double single atoms promotes the efficient utilization of metal resources. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 is the X-ray diffraction (XRD) diagram of the product of the embodiment of the present invention, and the product of the present invention is denoted as Ru SAs Pd SAs+NPs -CN, subscript SAs stands for single atom, and subscript NPs stands for nanoparticle. The semi-finished product obtained by thermal decomposition of ruthenium trichloride and urea, i.e., Ru single atom modified carbon nitride (Ru SAs -CN) is used as a comparison, and pure carbon nitride (CN) without any metal species modification is also used as a comparison. It can be seen from the figure that the introduction of Ru and Pd species does not change the crystal phase, and no impurity phase related to Ru and Pd is produced.

[0011] Figure 2 This is a Fourier transform infrared spectrum (FTIR) of the product of the embodiment of the present invention, CN and Ru SAs -CN is used as a comparison. It can be seen from the figure that the co-modification of Ru and Pd does not change the short-range order characteristics of the original CN.

[0012] Figure 3 (a) is a scanning electron microscope (SEM) image of the product of the embodiment of the present invention, for comparison, Figure 3 (b) is the SEM image of pure carbon nitride (CN). Figure 3 (c) is Ru single atom modified carbon nitride (Ru SAs -CN). It can be seen that the product is a two-dimensional sheet structure and the Ru and Pd modifications have basically not changed the morphology.

[0013] Figure 4 (a) is a transmission electron microscope (TEM) image of the product of the embodiment of the present invention, for comparison, Figure 4 (b) is the TEM image of pure carbon nitride (CN). Figure 4 (c) is Ru single atom modified carbon nitride (Ru SAs-CN) TEM image, Figure 4 (d, e) are high-resolution TEM images of the product of the embodiment of the present invention and corresponding lattice fringe intensity images, Figure 4 (f) is a particle size distribution diagram of nanoparticles on the product of the present invention. It can be further seen that the product is a two-dimensional sheet structure and the Pd nanoparticles are evenly distributed on the nanosheets with an average particle size of 4.20 nm. It should be noted that Figure 3 (a) Pd nanoparticles were not observed in the SEM image due to the limited SEM resolution.

[0014] Figure 5 The AFM image (a) and the corresponding height curve (b) of the product of the embodiment of the present invention are shown in Figure 1. It can be seen from the figure that the thickness of the product is about 1.8 nm and the presence of Pd nanoparticles is also confirmed.

[0015] Figure 6 This is a spherical aberration electron microscope (AC-HAADF-STEM) image of the product of the embodiment of the present invention ( Figure 6 (a)) and regional line scan analysis diagram ( Figure 6 (b)) and the corresponding elemental mapping ( Figure 6 (c)-(h)), for comparison, Figure 6 (i) is Ru single atom modified carbon nitride (Ru SAs These results confirm the elemental composition of the product, and it can be seen that Ru is uniformly distributed on the carbon nitride matrix in the form of single atoms and Pd in ​​the form of single atoms and nanoparticles.

[0016] Figure 7 is an X-ray photoelectron spectrum (XPS) diagram of the product of the embodiment of the present invention, ( Figure 7 (a)-(e)) and electron paramagnetic resonance (EPR) spectra ( Figure 7 (f)), pure carbon nitride (CN) and Ru single atom modified carbon nitride (Ru SAs -CN) as a comparison. These results further confirmed the elemental composition of the product, the valence state of Ru and Pd single atoms in the product, and the change of the coordination configuration of Ru single atoms.

[0017] Figure 8 ( Figure 8 (a)-(n)) are synchrotron radiation test analysis diagrams and calculation simulation diagrams of the product of the embodiment of the present invention ( Figure 8 (g, h, n) illustration and Figure 8 (o)), Ru single atom modified carbon nitride (Ru SAs -CN) as a comparison. Synchrotron radiation analysis mainly includes X-ray absorption near-edge structure spectroscopy ( Figure 8(a, i)), Fourier transform extended X-ray absorption fine structure spectroscopy ( Figure 8 (b, j)), wavelet transform-extended X-ray absorption fine structure spectroscopy ( Figure 8 (cf, km)) and the product extended X-ray absorption fine structure spectrum and its fitting curve ( Figure 8 (g, h, n)). These analysis results further show that Ru in the product is distributed in the form of single atoms, and Pd is distributed in the form of single atoms and nanoparticles, and the valence state of the Ru-Pd double single atom and the asymmetric low-coordinated Ru-N3 and Pd-N1 configurations are determined.

[0018] Fig. 9 The UV-visible absorption spectrum of the product of the embodiment of the present invention is Fig. 9 (a) and the corresponding (αhν) 1 / 2 Tauc for hν Fig. 9 (b) Pure carbon nitride (CN) and Ru single atom modified carbon nitride (Ru SAs -CN) as a comparison, the band gap of the product is 2.48eV.

[0019] Fig.10 The N2 adsorption-desorption curve and BET specific surface area and pore volume histogram (inset) of the product of the embodiment of the present invention, pure carbon nitride (CN) and Ru single atom modified carbon nitride (Ru SAs -CN) as a comparison.

[0020] Fig.11 The active diagram of the photocatalytic reduction of carbon dioxide to produce CO and CH4 of the product of the embodiment of the present invention, pure carbon nitride (CN) and Ru single atom modified carbon nitride (Ru SAs -CN) as a comparison. Fig.11 (a) is CO generation activity, Fig.11 (b) CH4 generation activity, Fig.11 (c) is the average generation activity of CO and CH4.

[0021] Fig.12 This is a stability diagram of the photocatalytic carbon dioxide reduction cycle of the product of the embodiment of the present invention. DETAILED DESCRIPTION

[0022] The following steps: (1) The molar ratio of ruthenium trichloride to urea is in the range of 1:150000-1:28000. For example, in the case of 50g urea and 360μL ruthenium trichloride solution (10mg / mL), the amount of ruthenium trichloride is about 0.01736mmol, the amount of urea is about 0.83250mol, and the molar ratio of ruthenium trichloride to urea is about 1:47955. The molar ratio of ruthenium trichloride to urea is between 1:150000-1:28000. This principle may be applied to the synthesis of other bimetallic single atoms and nanoparticles co-modified carbon nitride nanomaterials.

[0023] A proper amount of urea solution and ruthenium trichloride solution are prepared into a mixed aqueous solution (the solvent is water, i.e., urea aqueous solution, ruthenium trichloride aqueous solution) and transferred to a centrifuge tube for rapid freezing with liquid nitrogen, and then the frozen mixed solution is freeze-dried using a freeze dryer. This principle may be used to synthesize other bimetallic single atoms and nanoparticles co-modified carbon nitride nanomaterials. The powder obtained by freeze-drying and grinding the mixed solution of ruthenium trichloride and urea is transferred to an alumina crucible with a lid and wrapped with tin foil. The pyrolysis reaction is carried out in a muffle furnace at 550±20℃ for 3±1h, and the heating rate is 5℃ / min. After the reaction is completed and naturally cooled to room temperature, the product is collected after grinding; not wrapping with tin foil generally affects the yield, and covering or not covering the crucible generally affects the yield. Tin foil can be omitted, but at least it must be covered, otherwise the yield is very low and may also affect the product structure.

[0024] The powder obtained after the freeze-dried powder is ground is transferred to an alumina crucible with a lid and the crucible is wrapped with tin foil, and pyrolysis reaction is carried out in a muffle furnace at about 550°C for about 3 hours, with a heating rate of 5°C / min. After the reaction is completed, the powder is naturally cooled to room temperature, and the product is collected after being ground;

[0025] (2) placing an appropriate amount of the above product in an appropriate amount of 0.5 M sulfuric acid solution and magnetically stirring for about 24 hours, then centrifugally washing with deionized water and anhydrous ethanol until neutral and freeze-drying to obtain a Ru single atom modified carbon nitride semi-finished product.

[0026] (3) uniformly dispersing the semi-finished product and palladium nitrate dihydrate in anhydrous ethanol to obtain a suspension, which is then placed in an oven and dried to obtain a precursor product;

[0027] Specifically: disperse an appropriate amount of the above semi-finished product in an appropriate amount of anhydrous ethanol by ultrasonication for tens of minutes, add an appropriate amount of palladium nitrate dihydrate solution dropwise under vigorous magnetic stirring, and then continue stirring for 6±1h to obtain a uniformly dispersed suspension.

[0028] The suspension was placed in an oven at 70±10° C. and dried for 12±1 h, and then ground and collected to obtain a precursor product.

[0029] (4) The precursor product is placed in a covered quartz ark, and then annealed in a tube furnace at 300±20°C in an Ar atmosphere for 1.5±0.5h. After grinding, centrifugal washing and freeze-drying, asymmetric low-coordinated Ru-Pd bimetallic single atoms and Pd nanoparticles co-modified carbon nitride nanomaterials are obtained.

[0030] The mass ratio of the palladium nitrate dihydrate to the semi-finished product is in the range of 1:38-1:12. For example, in the case of 30 mg of the semi-finished product and 3 mL of palladium nitrate dihydrate solution (0.002M), the mass of palladium nitrate dihydrate is 1.59876 mg, and the mass ratio of palladium nitrate dihydrate to the semi-finished product is about 1:19. The mass ratio of the metal salt to the semi-finished product is between 1:38-1:12. This principle may be applied to the synthesis of other asymmetric low-coordinated bimetallic single atoms and nanoparticles co-modified carbon nitride nanomaterials.

[0031] Place an appropriate amount of the above precursor product in a covered quartz ark, and then place it in a tube furnace for annealing at 300±20℃ for about 1.5h, with a heating rate of 5℃ / min, an Ar atmosphere, and a gas flow rate of 80±5mL / min. After the reaction is completed and naturally cooled to room temperature, take out the product and grind it for collection.

[0032] The tubular furnace annealing product was washed several times with anhydrous ethanol and deionized water, and then placed in a freeze dryer for freeze drying for 4-6 days. Thus, asymmetric low-coordinated Ru-Pd bimetallic single atoms and Pd nanoparticles co-modified carbon nitride nanomaterials were obtained, which can achieve good results in photocatalysis.

[0033] (1) Under dry conditions, weigh 50 g of urea and dissolve it in 50 mL of deionized water under magnetic stirring until it becomes clear and transparent;

[0034] (2) Using a pipette, measure 360 ​​μL of ruthenium trichloride solution (10 mg / mL), add it dropwise into the above urea solution under magnetic stirring, and continue stirring for 3 h;

[0035] (3) After stirring, the mixed solution was transferred to a centrifuge tube and rapidly frozen with liquid nitrogen, and then placed in a freeze dryer for freeze drying for several days;

[0036] (4) The freeze-dried powder was ground in an agate mortar for 30 min, then transferred to an alumina crucible with a lid and wrapped with tin foil, then placed in a muffle furnace and heated to 550°C at a heating rate of 5°C / min for pyrolysis reaction for 3 h. After the reaction was completed and naturally cooled to room temperature, the pyrolysis product was taken out and ground and collected;

[0037] (5) 0.2 g of the above pyrolysis product was placed in 35 mL of 0.5 M sulfuric acid solution and ultrasonically treated for 30 min, and then magnetically stirred at a certain speed for 24 h;

[0038] (6) The sulfuric acid-treated product was first centrifuged and washed with deionized water until neutral, and then centrifuged and washed several times with anhydrous ethanol and deionized water, respectively, and then freeze-dried in a freeze dryer for several days to obtain Ru single-atom modified carbon nitride (Ru SAs -CN) semi-finished products;

[0039] (7) Weigh 30 mg of the above-mentioned Ru single atom modified carbon nitride (Ru SAs -CN) semi-finished product was ultrasonically dispersed in 10 mL of anhydrous ethanol, and then 3 mL of 0.002 M palladium nitrate dihydrate solution was measured with a pipette and added dropwise into the anhydrous ethanol dispersion of the semi-finished product under vigorous magnetic stirring and stirred for 6 h to obtain a suspension containing palladium nitrate;

[0040] (8) The suspension containing palladium nitrate was placed in a forced air drying oven at 70° C. and dried for 12 h, and then the dried product was transferred to an agate mortar and ground for several minutes before collection;

[0041] (9) The dried product was transferred into a quartz ark with a lid, and then placed in a tube furnace in an Ar atmosphere for annealing at 300 °C for 1.5 h, with a heating rate of 5 °C / min and a gas flow rate of 80 mL / min. After the reaction was completed and naturally cooled to room temperature, the product was taken out, ground and collected;

[0042] (10) The above-mentioned tube furnace annealing product was centrifugally washed several times with anhydrous ethanol and deionized water, and then placed in a freeze dryer for freeze drying for 4-6 days to obtain asymmetric low-coordinated Ru-Pd bimetallic single atoms synergistic with Pd nanoparticles co-modified carbon nitride (Ru SAs Pd SAs+NPs The obtained asymmetric low-coordinated Ru and Pd bimetallic single atoms cooperate with Pd nanoparticles to co-modify carbon nitride nanomaterials, which can achieve good results in photocatalysis.

[0043] The product was analyzed by X-ray diffractometer (XRD), Fourier transform infrared spectrometer (FTIR), scanning electron microscope (SEM), transmission electron microscope (TEM), atomic force microscope (AFM), spherical aberration electron microscope (AC-HAADF-STEM), X-ray photoelectron spectrometer (XPS), electron paramagnetic resonance spectrometer (EPR), Shanghai Synchrotron Radiation Facility (SSRF), ultraviolet-visible diffuse reflectance spectrometer (UV-vis DRS), fully automatic specific surface area and porosity analyzer, and inductively coupled plasma atomic emission spectrometer (ICP-OES).

[0044] Figure 1 is the XRD diagram of the product of the embodiment of the present invention, and the product of the present invention is denoted as Ru SAs Pd SAs+NPs -CN, the subscript SAs stands for single atom, and the subscript NPs stands for nanoparticle. The semi-finished product obtained by thermal decomposition of ruthenium trichloride and urea, i.e., Ru single atom modified carbon nitride (Ru SAs -CN) is compared with pure carbon nitride (CN) without any metal species modification. It can be seen from the figure that the introduction of Ru and Pd species does not change the crystal phase, and no impurity phase related to Ru and Pd is produced.

[0045] Table 1 is the ICP-OES test results of the product of the embodiment of the present invention, Ru single atom modified carbon nitride (Ru SAs -CN) semi-finished product is used as a comparison. It can be seen from the table that the actual contents of Ru and Pd in ​​the product are 0.0214wt% and 1.2911wt%, respectively, and the introduction of Pd hardly changes the Ru content of the original semi-finished product.

[0046] Figure 2 This is the FTIR graph of the product of the embodiment of the present invention, CN and Ru SAs -CN is used as a comparison. It can be seen from the figure that the co-modification of Ru and Pd does not change the short-range order characteristics of the original CN.

[0047] Figure 3 (a) is a SEM image of the product of the embodiment of the present invention, for comparison, Figure 3 (b) is the SEM image of pure carbon nitride (CN). Figure 3 (c) is Ru single atom modified carbon nitride (Ru SAs -CN). It can be seen that the product is a two-dimensional sheet structure and the Ru and Pd modifications have basically not changed the morphology.

[0048] Figure 4 (a) is a TEM image of the product of the embodiment of the present invention, for comparison, Figure 4 (b) is the TEM image of pure CN. Figure 4 (c) YesRu SAs TEM image of -CN, Figure 4 (d, e) are high-resolution TEM images of the product of the embodiment of the present invention and corresponding lattice fringe intensity images, Figure 4 (f) is a particle size distribution diagram of nanoparticles on the product of the present invention. It can be further seen that the product is a two-dimensional sheet structure and the Pd nanoparticles are evenly distributed on the nanosheets with an average particle size of 4.20 nm. It should be noted that Figure 3 (a) Pd nanoparticles were not observed in the SEM image due to the limited SEM resolution.

[0049] Figure 5 AFM of the embodiment of the present invention Figure 5 (a) and the corresponding height curve Figure 5 (b) It can be seen from the figure that the product thickness is about 1.8nm and the presence of Pd nanoparticles is also confirmed.

[0050] Figure 6 AC-HAADF-STEM image of the product of the embodiment of the present invention ( Figure 6 (a)) and regional line scan analysis diagram ( Figure 6 (b)) and the corresponding elemental mapping ( Figure 6 (c)-6(h)), for comparison, Figure 6 (i) is Ru SAs AC-HAADF-STEM image of -CN. These results confirm the elemental composition of the product, and it can be seen that Ru is uniformly distributed on the carbon nitride support in the form of single atoms and Pd in ​​the form of single atoms and nanoparticles.

[0051] Figure 7 This is the XPS picture of the product of the embodiment of the present invention ( Figure 7 (a)-(e)) and EPR diagrams ( Figure 7 (f)), pure CN and Ru SAs -CN was used as a comparison. These results further confirmed the elemental composition of the product, the valence state of Ru and Pd single atoms in the product, and the change in the coordination configuration of Ru single atoms.

[0052] Figure 8 This is a synchrotron radiation test analysis diagram of the product of the embodiment of the present invention ( Figure 8 (a)-(n)) and computational simulation diagrams ( Figure 8 (g, h, n) and Figure 8 (o)), Ru SAs -CN as a comparison. Synchrotron radiation analysis mainly includes X-ray absorption near-edge structure spectroscopy ( Figure 8 (a, i)), Fourier transform extended X-ray absorption fine structure spectroscopy ( Figure 8 (b, j)), wavelet transform-extended X-ray absorption fine structure spectroscopy ( Figure 8 (cf, km)) and the product extended X-ray absorption fine structure spectrum and its fitting curve ( Figure 8 (g, h, n)). These analysis results further show that Ru in the product is distributed in the form of single atoms, and Pd is distributed in the form of single atoms and nanoparticles, and the valence state of the Ru-Pd double single atom and the asymmetric low-coordinated Ru-N3 and Pd-N1 configurations are determined.

[0053] Fig. 9 The UV-vis absorption spectrum of the product of the embodiment of the present invention is Fig. 9(a) and the corresponding (αhν) 1 / 2 Tauc for hν Fig. 9 (b), pure CN and Ru SAs -CN is used as a comparison. From the analysis of the figure, it can be seen that the band gap of the product is 2.48eV.

[0054] Fig.10 The N2 adsorption-desorption curve and BET specific surface area and pore volume histogram (inset) of the product of the embodiment of the present invention, pure CN and Ru SAs -CN as a comparison, it can be seen that the specific surface area and pore volume of the product are compared with pure CN and Ru SAs -CN has increased to a certain extent.

[0055] Application example: the asymmetric low-coordinated Ru-Pd bimetallic single atom prepared in the embodiment cooperates with Pd nanoparticles to co-modify carbon nitride (Ru SAs Pd SAs+NPs -CN) nano-photocatalyst was used to conduct photocatalytic CO2 reduction experiment. Specifically, 5 mg of photocatalyst was weighed and evenly dispersed in 3.14 cm 2 The reaction system was placed on a porous quartz glass sheet and placed in a Pyrex glass reaction container. The volume of the entire reaction system was about 460 mL, and the light source was a 300 W xenon lamp. High-purity CO2 gas was then injected into the reaction system, the air was evacuated and the pressure in the reaction system reached standard atmospheric pressure. Subsequently, 400 μL of deionized water was injected into the reaction system as a reducing agent, and the light was turned on after the catalyst adsorbed and balanced the reactants in the dark for several hours. After that, about 1 mL of gas was taken out from the reaction system every hour and injected into a gas chromatograph to analyze the amount of CO and CH4 produced.

[0056] The evolution of CO and CH4 production over time and the product yields are shown in Fig.11 The results show that the asymmetric low-coordinated Ru-Pd bimetallic single atoms synergistically with Pd nanoparticles co-modified carbon nitride nanophotocatalyst has a higher photocatalytic performance than pure carbon nitride (CN) and Ru single atom modified carbon nitride (Ru SAs -CN) has better photocatalytic reduction activity for CO2. While the activity is effectively improved, the product still maintains high selectivity for photocatalytic reduction of CO2 to CO( Fig.11 ).

[0057] The photocatalytic CO2 reduction stability of the product is as follows Fig.12 As shown in the figure, it can be seen that the asymmetric low coordination

[0058] Ru-Pd bimetallic single atoms synergistic with Pd nanoparticles to co-modify carbon nitride nanophotocatalysts for photocatalytic reduction

[0059] CO2 has excellent stability.

[0060] Table 1 Description

[0061] Table 1 is the ICP-OES test results of the products of the present invention. SAs -CN as a comparison, it can be seen from the table that the actual contents of Ru and Pd in ​​the product are 0.0214wt% and 1.2911wt% respectively.

[0062] Table 1 shows the contents of metal elements Ru and Pd in ​​the catalysts synthesized in the examples. SAs -CN for comparison.

[0063]

[0064] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A method for preparing carbon nitride co-modified by Ru-Pd bimetallic single atoms and Pd nanoparticles, characterized in that: The method comprises the following steps: (1) using two precursor materials, ruthenium trichloride and urea, in a molar ratio of 1:150000-1:28000 to prepare a mixed aqueous solution, transferring the mixed solution to a centrifuge tube and rapidly freezing it with liquid nitrogen, then freeze-drying the frozen mixed solution using a freeze dryer, grinding the obtained powder, transferring it to an alumina crucible with a lid and wrapping it with tin foil, and then performing a pyrolysis step to obtain a precursor, wherein the pyrolysis condition is to perform a pyrolysis reaction in a muffle furnace at 550±20°C for 3±1h, and the product is collected after being ground; (2) placing the product in a 0.5M sulfuric acid solution and subjecting it to magnetic stirring for about 24h, then centrifugally washing it to neutrality and freeze-drying it to obtain a Ru single atom modified carbon nitride semi-finished product; (3) The semi-finished product is redispersed in anhydrous ethanol, and palladium nitrate dihydrate solution is added dropwise under magnetic stirring and stirring is continued for 6±1h, wherein the mass ratio of palladium nitrate dihydrate to the semi-finished product is 1:38-1:12; the resulting suspension is placed in an oven at 70±10°C and dried for 12±1h; (4) The dried powder is transferred to a quartz ark with a lid, and annealed in a tube furnace at 300±20°C in an Ar atmosphere for 1.5±0.5h, and then ground, centrifuged and washed, and freeze-dried to obtain Ru-Pd bimetallic single atoms and Pd nanoparticles co-modified carbon nitride nanomaterials.

2. The method for preparing Ru and Pd bimetallic single atoms in cooperation with Pd nanoparticles co-modified carbon nitride according to claim 1, characterized in that: (1), the mixed solution is prepared by adding a proper amount of ruthenium trichloride solution dropwise into a proper amount of urea solution, and continuously stirring the mixture by magnetic force for several hours to obtain a uniform mixed solution of ruthenium trichloride and urea, wherein the molar ratio of ruthenium trichloride to urea is 1:150000-1:28000.

3. The method for preparing Ru-Pd bimetallic single atom and Pd nanoparticle co-modified carbon nitride according to claim 1, characterized in that: The mixed solution of ruthenium trichloride and urea was transferred into a centrifuge tube and rapidly frozen with liquid nitrogen, and then freeze-dried in a freeze dryer for several days.

4. The method for preparing Ru-Pd double single atoms and Pd nanoparticles co-modified carbon nitride according to any one of claims 1 to 3, characterized in that: The powder obtained by freeze-drying the above mixed solution was transferred to an agate mortar and ground for tens of minutes, then transferred to an alumina crucible with a lid and wrapped with several layers of tin foil, and then placed in a muffle furnace for pyrolysis reaction at 550±20℃ for about 3h with a heating rate of 5℃ / min. After the reaction was completed and naturally cooled to room temperature, the product was collected after grinding.

5. The method for preparing carbon nitride co-modified by Ru-Pd bimetallic single atoms and Pd nanoparticles according to any one of claims 1 to 3, characterized in that: The pyrolysis product was placed in a 0.5 M sulfuric acid solution and first ultrasonically treated for about 30 min, and then magnetically stirred at a certain speed for 24±2 h.

6. The method for preparing carbon nitride co-modified by Ru-Pd bimetallic single atoms and Pd nanoparticles according to any one of claims 1 to 3, characterized in that: The sulfuric acid-treated product is first washed with deionized water until neutral, and then washed several times with anhydrous ethanol and deionized water respectively, and then freeze-dried in a freeze dryer for several days, especially 4-6 days, to obtain a Ru single-atom modified carbon nitride semi-finished product.

7. The method for preparing carbon nitride co-modified with Ru-Pd bimetallic single atoms and Pd nanoparticles according to any one of claims 1 to 3, characterized in that: An appropriate amount of the above-mentioned semi-finished product is re-ultrasonic dispersed in anhydrous ethanol, and then an appropriate amount of palladium nitrate dihydrate solution is added dropwise under vigorous magnetic stirring and stirred for 6±1h to obtain a suspension containing palladium nitrate uniformly dispersed therein, wherein the mass ratio of palladium nitrate dihydrate to the semi-finished product is 1:38-1:

12.

8. The method for preparing carbon nitride co-modified by Ru and Pd bimetallic single atoms in cooperation with Pd nanoparticles according to any one of claims 1 to 3, characterized in that: The suspension containing palladium nitrate was placed in a forced air drying oven at 70±10°C for 12±1h, and then the dried product was transferred to an agate mortar and ground for several minutes before collection.

9. The method for preparing carbon nitride co-modified with Ru-Pd bimetallic single atoms and Pd nanoparticles according to any one of claims 1 to 3, characterized in that: The product dried in the blast drying oven was transferred to a quartz ark with a lid, and then placed in a tubular furnace in an Ar atmosphere and annealed at 300±20°C for about 1.5 h, with a heating rate of 5°C / min and a gas flow rate of 80±5mL / min. After the reaction was completed and naturally cooled to room temperature, the product was taken out, ground and collected.

10. The method for preparing carbon nitride co-modified by Ru and Pd bimetallic single atoms in cooperation with Pd nanoparticles according to any one of claims 1 to 3, characterized in that: Weighing and grinding are carried out in a dry environment.